Awareness of patients’ orthodontic problems and referral practices among general dental practitioners and non-orthodontic specialists - Abdullah Kamran, Muhammad; Ahmed Saddah, Rawan; Mohammed Alasmari, Afnan; Almoammar, Salem; A Alnazeh, Abdullah; Alshahrani, Ibrahim (Vojnosanitetski pregled, 2022)
Background/Aim. Dentists and particularly general dental practitioners (GDPs) should be able to identify problems such as malocclusions and refer patients with such problems to orthodontics. The aim of the study was to evaluate the awareness of orthodontic problems and referral practices among GDPs and non-orthodontic specialists practicing in the Kingdom of Saudi Arabia. Methods. A cross-sectional prospective study included GDP and specialists/consultants of both genders, aged between 22–60 years, practicing general dentistry and specialists other than orthodontics who had worked in their field for two or more years. Non-practicing dentists and nonregistered dentists were excluded. Data was analyzed on SPSS version 21.00. Results. Among the respondents, 55.5% were men, and 44% were GDPs. Out of the total number of respondents, 107 (53.5%) GDPs and 66 (33%) non-orthodontic specialists practiced orthodontic referral in their practices. By using the χ2 test, statistical analysis of different variables depending on the participants’ gender and specialty was performed. It revealed that variables with significant p-value were: orthodontist referral, the recommendation of orthodontic treatment only after the eruption of all permanent teeth, awareness of tooth extraction for alignment of irregular teeth, and awareness regarding worsening of temporomandibular joint problems by orthodontic treatment. Conclusion. The referral practices of dentists practicing in the Kingdom of Saudi Arabia concerning orthodontic patients were satisfactory, although awareness regarding orthodontic problems requires continuous learning and considerate positive progression toward basic orthodontics.